Governmental WEB-Sites and Citizens' Empowerment for Knowledge Society in Countries Aspiring for EU Membership - Božić, Jasmina (Array, 2006)
Abstract The paper aims at examining the actualisation of information technologies' (IT) indisputable potential to substantially contribute to citizens' empowerment and knowledge society, in countries aspiring for membership of the European Union, through investigating quality, quantity, accessibility and usability of information offered at governmental web-sites. The research sample is purposive and comprises the web-sites of Croatian, Serbian and Bosnian Governments as well as that of the U.S. Government as a role-model. Data are gathered through four-domain framework relating to citizen-orientedness, connectedness, structure transparency and information technologies, each containing specific indicators. The research results show that the respective Southeast European Governments have significantly advanced the conceptual frameworks and actual applications of their virtual presentations. Each of them introduced the web-policy of data accessibility, data consistency, data currency, high technical standards, support to users, and other web-development pillars. The comparative analysis indicated that certain services to citizens yet need to be included in the three Governments' sites, and online services may be further personalised in form and content.